The influence of the electron transport layer on charge dynamics and trap-state properties in planar perovskite solar cells. Issue 21 (26th March 2020) - Yu, Man; Guo, Yanru; Yuan, Shuai; Zhao, Jia-Shang; Qin, Yujun; Ai, Xi-Cheng
Abstract : The underlying work mechanism of electron transport layers and their significant influence on photovoltaic performance are systematically studied. Abstract : Despite the outstanding photovoltaic performance of perovskite solar cells, the correlation between the electron transport layer and the mechanism of photoelectric conversion is still not fully understood. In this paper, the relationship between photovoltaic performance and carrier dynamics is systematically studied in both TiO2 - and SnO2 -based planar perovskite devices. It is found that the different electron transport layers result in distinct forward scan results and charge dynamics. Based on the charge dynamics results, the influence of the electron transport layer on charge carrier transport and charge recombination is revealed. More importantly, the trap-state density is characterized, which is proven to be related to the charge carrier dynamics and the specific hysteresis behaviour in the perovskite solar cells. The present work would provide new insights into the working mechanisms of electron transport layers and their effect on hysteresis.